A Strategi Pembiayaan Perbankan Syariah Dalam Mendukung Keuangan Inklusif Bagi Sektor Mikro studi kasus PT. BPRS Gebu Prima Medan - Mely Nur Afrilia (STEI Kanjeng Sepuh Gresik Jawa Timur, 2023)
Abstract At PT. BPRS Gebu Prima Medan from the last 5 years the company has produced a declining total of customers for financing products, even though BPRS Gebu Prima has carried out various promotions but it is still arguably ineffective. This study aims to see how the financing strategy of BPRS Gebu Prima Medan, what are the obstacles that occur in financing for the micro sector as well as solutions and solutions using SWOT analysis at PT BPRS Gebu Prima Medan. The research method used is qualitative, namely by using interview technique research steps to obtain descriptive information, namely analyzing various internal factors to see factors outside the company to see the opportunities and constraints generated in a company. And what is displayed from the respondents in writing and also verbally and the resulting behavior. From the findings of applying the SWOT technique through internal and external factors, it shows that this is in the type of quadrant I, namely positive, namely conditions that generate profits because they have opportunities and abilities so that they can use the opportunities they have optimally. And using this method encourages regulation to grow and develop significantly. The analysis of constraints in financing in the micro sector using SWOT has been adjusted to bank laws and an Islamic perspective for implementation that does not contain various elements that are not permissible for Islamic banks. And to deal with threats, banks will carry out risk management for financing using rescheduling, reconditioning and restructuring efforts. Keywords: Financing, Inclusive Finance, UMKM, SWOT